2018
DOI: 10.3390/cancers10040110
|View full text |Cite
|
Sign up to set email alerts
|

New Challenges in Targeting Signaling Pathways in Acute Lymphoblastic Leukemia by NGS Approaches: An Update

Abstract: The identification and study of genetic alterations involved in various signaling pathways associated with the pathogenesis of acute lymphoblastic leukemia (ALL) and the application of recent next-generation sequencing (NGS) in the identification of these lesions not only broaden our understanding of the involvement of various genetic alterations in the pathogenesis of the disease but also identify new therapeutic targets for future clinical trials. The present review describes the main deletions, amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 110 publications
4
38
0
Order By: Relevance
“…In B-ALL, RAS signaling (NRAS, KRAS, PTPN11, FLT3, NF1, et al) and B-cell differentiation and development (PAX5, IKZF1, EBF1, et al) are the most common pathogenic pathways [11,22], and we found a similar distribution of genetic changes in this study. In the adult high-risk cytogenetic group, IKZF1 deletion was the most common alteration (6/12, 50%).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In B-ALL, RAS signaling (NRAS, KRAS, PTPN11, FLT3, NF1, et al) and B-cell differentiation and development (PAX5, IKZF1, EBF1, et al) are the most common pathogenic pathways [11,22], and we found a similar distribution of genetic changes in this study. In the adult high-risk cytogenetic group, IKZF1 deletion was the most common alteration (6/12, 50%).…”
Section: Discussionsupporting
confidence: 83%
“…From a literature review, we selected 500 genes found to be signi cantly mutated in ALL (Additional le 1: Table S1). Our gene panel included [11]: cell cycle and p53 signaling pathway (ATM, CDKN1B, CDKN2A, CDKN2B, RB, TP53, et al), chromatin structure modi ers and epigenetic regulators (ARID1A, BMI1, CHD1, CHD4, CHD9, CREBBP, CTCF, DNMT3A, EED, EP300, EZH2, KDM5C, KDM6A, et al), JAK-STAT signaling pathway (CRLF2, IL2RB, IL7R, JAK1, JAK2, JAK3, PTPN2, SH2B3, STAT3, TYK2, et al…”
Section: Gene Panelmentioning
confidence: 99%
“…Class IA PI3Ks (PIK3CA, PIK3CB and PIK3CD), are constituted from a p110 catalytic unit and a p85 regulatory one, and are the most important isoforms in cancer studies. PI3Ks are activated by different agents; PI3Kα, β and δ are activated when the extracellular ligands bind to one of the transmembrane glycoproteins with enzymatic activity called receptor tyrosine kinases (RTKs), while PI3Kγ is activated by G-protein-coupled receptors (GPCRs) and by the RAS family of GTPases ( 13 - 15 ).…”
Section: Structure and Functionmentioning
confidence: 99%
“…Current advances suggest a therapeutic role of epigenetic enzymes, such as DNA methyltransferases and histone deacetylases, with promising results for leukemia patients [ 6 , 24 ]. For instance, it has been suggested that the inhibition of the histone H3K27 demethylase UTX shows promising antitumor effects in T-ALL, while the activity of H3K27 methyltransferase EZH2 acts as tumor suppressor in ALL mouse models [ 25 , 26 ]. Other critical enzymes involved in tumor progression are the H3K9 methyltransferases.…”
Section: Discussionmentioning
confidence: 99%